4 Sifat Nabi Muhammad Dalam Penegakan Etika Akuntan - Ira Farlizanty Tri Rahadi (Shafin: Sharia Finance and Accounting Journal, 2025)
This study aims to examine the application of the Indonesian accountant code of ethics in the practice of the public accounting profession, focusing on the role of ethical values taught by the Prophet Muhammad as a guide in improving compliance with the professional code of ethics. Although the code of ethics has been regulated by professional institutions such as IAPI, IAI, and IAMI, there are still many violations that occur, such as in the bribery case involving the auditor of the Bogor Regent in 2022. This research proposes that the noble traits of the Prophet Muhammad, namely siddiq (honest), amanah (trustworthy), fathanah (intelligent), and tabligh (conveying) can be integrated in accounting practices to overcome ethical problems in this profession. This research uses a library research approach with a narrative method to analyze and explore the relationship between these ethical values and the application of the accountant's code of ethics. The results of the study are expected to provide new insights for the enforcement of ethics in the accounting profession in Indonesia, by adding a religious perspective in applying the existing code of ethics. By emulating the characteristics of the Prophet Muhammad, it is hoped that accountants can increase their professionalism and integrity in carrying out their duties, and improve the image of the accounting profession in the eyes of the public.